2023
DOI: 10.52326/jss.utm.2022.5(4).07
|View full text |Cite
|
Sign up to set email alerts
|

Struggle for Sustainable Public Transport in Southwestern Nigerian Cities

Abstract: Public transport contributes significantly to the development of socioeconomic activities and the long-term sustainability of all communities worldwide. Undoubtedly, it is a catalyst for maximizing quality urban living, social service accessibility, and environmental balance. Despite its considerable importance and benefits, public transport in Nigeria is still poorly practiced, and plagued by complex operational challenges. Based on this context, we assessed the public transport systems in Ikeja-Lagos, Abeoku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Tourism remains a vital component of the economies of many major destination cities and nations around the world [27,29]. Considering the importance of tourism to national development, countries endowed with many natural tourist attractions and destinations continue to invest in the sector to boost not only the tourism development, experiences, image, and sustainability of tourism activities in diverse ways but also open opportunities for economic diversification, improved quality of life, and sustainability of the ecosystem [8,26]. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tourism remains a vital component of the economies of many major destination cities and nations around the world [27,29]. Considering the importance of tourism to national development, countries endowed with many natural tourist attractions and destinations continue to invest in the sector to boost not only the tourism development, experiences, image, and sustainability of tourism activities in diverse ways but also open opportunities for economic diversification, improved quality of life, and sustainability of the ecosystem [8,26]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ref. [8,26] observed that tourism has the potential to diversify the economy and reduce dependence on traditional industries, including agriculture, manufacturing, and the public health sector. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations